2002
DOI: 10.1093/ndt/17.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Significance of high C-reactive protein levels in pre-dialysis patients

Abstract: The prevalence of inflammation is high in pre-dialysis patients. High serum CRP levels predict a constant inflammatory state on follow-up. As occurs in dialysis patients, pre-dialysis inflammation predicts lower serum albumin concentration, poorer response to Epo, and a higher hospitalization rate. The decline in renal function does not seem to be related to the inflammatory state. Mortality was not affected on short-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 20 publications
8
69
2
1
Order By: Relevance
“…Probably, inflammation could be related to some factors, frequently associated with renal failure, which can worsen with the worsening of renal function. In this study (Ortega et al, 2002), CRP levels were higher in those patients with a previous history of CVD. Comparing with patients with normal CRP levels at baseline, patients with higher levels maintained significant higher levels on follow-up.…”
Section: Possible Causes Of Inflammationsupporting
confidence: 44%
See 2 more Smart Citations
“…Probably, inflammation could be related to some factors, frequently associated with renal failure, which can worsen with the worsening of renal function. In this study (Ortega et al, 2002), CRP levels were higher in those patients with a previous history of CVD. Comparing with patients with normal CRP levels at baseline, patients with higher levels maintained significant higher levels on follow-up.…”
Section: Possible Causes Of Inflammationsupporting
confidence: 44%
“…Another possibility could be that uremia by itself could be the cause of inflammation among these patients. However, in another study performed in pre-dialysis patients with a more homogeneous clearance of creatinine (Ortega et al, 2002), a non-normal distribution of CRP levels were detected. That means that only a group of patients with advanced renal failure shows high levels of CRP, whereas other patients with the same degree of renal insufficiency have even normal CRP values.…”
Section: Possible Causes Of Inflammationmentioning
confidence: 87%
See 1 more Smart Citation
“…Inflammation is a highly prevalent condition among CKD patients. Crosssectional studies have shown that 30-50% of nondialysis (Ortega et al, 2002) and dialysis (Docci et al, 1990;McIntyre et al, 1997) patients present serologic evidence of an activated inflammatory response with elevated serum concentration of C-reactive protein (CRP). Our group has recently reported increased REE in nondialysis patients with CRP40.5 mg/dl (Avesani et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…12 Hypo-albuminemia is highly predictive of future mortality risk when present at the time of initiation of chronic dialysis, as well as during the course of maintenance dialysis (MD). [13][14][15][16] It is considered that a decreased albumin level at the pre-dialysis stage with early CKD will translate into high malnutrition levels at the time these patients would require RRT.…”
mentioning
confidence: 99%